Impact of raw cocoa and chocolate on lipid profile and liver function in alcohol-induced toxicity Wister rats - Saleh, Alaa; Sabahelkhier, Murwan (International Journal of Medicine, 2017)
The aim of study is to evaluate the impact of raw cocoa and processed cocoa (galaxy chocolate) in the treatment of alcoholic fatty liver compare to prednisolone drug as common medication to treat fatty liver and carried out in Al-Neelain University in 2016. Eighteen female Wister rats were classified into six groups: Group one represented negative (H2O), Group two positive controls (0.5 ml/40% alcohol), Group three represented doses of 0.67g\kg raw cocoa, Group four represented dose of 1.35 g/kg raw cocoa, Group five represent dose of 5.4 g/kg galaxy chocolate, Group six received dose of 4.8 mg/kg prednisolone. The results show that the cocoa with low and high doses, galaxy chocolate and prednisolone significantly reduce the ALT, AST and GGT, and a significant decrease in the ALT level after administration of prednisolone drug when compared high cocoa dose group. Whereas, Galaxy chocolate significantly reduce the AST compared to low dose cocoa treated group. Also there is a significant increase in HDL and decrease in Total cholesterol, Triglycerol and low density lipoprotein in all treated groups compared to positive control. The ratio between Triglycerol: HDL and LDL: HDL show a significant reduction in group treated with galaxy chocolate compared to other treated groups. The results concluded that, cocoa in both forms raw and processed are efficient in the treatment of alcoholic fatty liver in comparison with prednisolone drug.